The Microbiota Determines Susceptibility to Experimental Autoimmune Uveoretinitis - Heissigerova, Jarmila; Seidler Stangova, Petra; Klimova, Aneta; Svozilkova, Petra; Hrncir, Tomas; Stepankova, Renata; Kverka, Miloslav; Tlaskalova-Hogenova, Helena; Forrester, John V (Journal of immunology research, 2016)
The microbiota is a crucial modulator of the immune system. Here, we evaluated how its absence or reduction modifies the inflammatory response in the murine model of experimental autoimmune uveoretinitis (EAU). We induced EAU in germ-free (GF) or conventionally housed (CV) mice and in CV mice treated with a combination of broad-spectrum antibiotics either from the day of EAU induction or from one week prior to induction of disease. The severity of the inflammation was assessed by fundus biomicroscopy or by histology, including immunohistology. The immunophenotyping of T cells in local and distant lymph nodes was performed by flow cytometry. We found that GF mice and mice where the microbiota was reduced one week before EAU induction were protected from severe autoimmune inflammation. GF mice had lower numbers of infiltrating macrophages and significantly less T cell infiltration in the retina than CV mice with EAU. GF mice also had reduced numbers of IFN-γ and IL-17-producing T cells and increased numbers of regulatory T cells in the eye-draining lymph nodes. These data suggest that the presence of microbiota during autoantigen recognition regulates the inflammatory response by influencing the adaptive immune response.
Keywords: interferon gama; Retinitis; Retinol-Binding Proteins; Interferon-gamma; bakteriální nálož; průtoková cytometrie; Anti-Bacterial Agents; Uveitis; Autoantigens; Bacterial Load; Interleukin-17; Disease Models, Animal; myši inbrední C57BL; mužské pohlaví; retinitida; regulační T-lymfocyty; Mice; oční proteiny; retina; gnotobiologické modely; Autoimmune Diseases; Microbiota; mikrobiota; Flow Cytometry; T-Lymphocytes, Regulatory; Eye Proteins; Macrophages; aktivace lymfocytů; Retina; Adaptive Immunity; modely nemocí na zvířatech; ženské pohlaví; zvířata; Lymphocyte Activation; proteiny vázající retinol; Germ-Free Life; autoantigeny; Eye; antibakteriální látky; interleukin-17; myši; makrofágy; oči; uveitida; Female; adaptivní imunita; Mice, Inbred C57BL; autoimunitní nemoci; Male; Animals